March - Brooks, Geraldine (Australia Harper Perennial, 2006)
The story of the absent father from Louisa May Alcott's "Little Women" and conjures a world of brutality, stubborn courage and transcendent love.
Keywords: United States -- American Civil War (1861-1865) -- March family (Fictitious characters)